Recent Trends in Nanomaterial-Based Biosensors for Point-of-Care Testing - Wang, Xu; Li, Feng; Guo, Yirong (Frontiers in Chemistry, 2020)
In recent years, nanomaterials of different shape, size, and composition have been prepared and characterized, such as gold and silver nanoparticles, quantum dots, mesoporous silica nanoparticles, carbon nanomaterials, and hybrid nanocomposites. Because of their unique physical and chemical properties, these nanomaterials are increasingly used in point-of-care testing (POCT) to improve analytical performance and simplify detection process. They are used either as carriers for immobilizing biorecognition elements, or as labels for signal generation, transduction and amplification. In this commentary, we highlight recent POCT technologies that employ nanotechnology for the analysis of disease biomarkers, including small-molecule metabolites, enzymes, proteins, nucleic acids, cancer cells, and pathogens. Recent advances in lateral flow tests, printable electrochemical biosensors, and microfluidics-based devices are summarized. Existing challenges and future directions are also discussed.